Ethanol Gas Sensor Fabrication Based on ZnO Flower Like Nanorods - Abdulqader Faisal; Mofeed Jaleel; Fahad Kamal (Engineering and Technology Journal, 2020)
Zinc oxide flower-like nanorods (ZnO NRs) was successfully synthesized via the hydrothermal method. The growth process was conducted with seed layer concentrations of 20mM. The as-synthesized nanostructures were characterized by x-ray diffraction (XRD), scanning electron microscope (SEM), atomic force microscope (AFM), and ultraviolet-visible (UV-VIS) spectrophotometer. The analysis results revealed a pure Wurtzite ZnO hexagonal nanostructures with preferred orientation (002) along the c-direction. The calculated band gap of average crystallite size is 3.2eV and 25 nm respectively. New designed, constructed and successfully calibrated for ethanol gas sensing was found. The ethanol gas sensor was fabricated at room temperature based on the ZnO NRs film. The synthesized materials proved to be a good candidate for the ethanol gas sensor. The optimum results of the gas sensor measurements of the synthesized gas sensor are as follows, the sensitivity, response time, and recovery time at 25 °C are 60%, 80 Seconds and 80 seconds respectively, and at 200 °C are 70%, 60 seconds and 50 seconds respectively.